Fuzzy Enhanced Intrusion Prevention System for Ad hoc Networks - S. Srinivasan, N. Ramya, V. Gokula Krishnan (International Journal of Advanced Science and Technology, 2020)
Mobile nodes in the MANET are randomly moving and it is easily compromised by the external attackers. Previous schemes were not able to find the intruders efficiently. In this research work, Fuzzy enhanced Intrusion Prevention System for detecting and isolating attackers in ad hoc network. It contains two phases. In first phase, broadcast routing is established from source to sink node. Fuzzy mechanism is established in the routing to obtain any malfunction present in the network. Fuzzy decision mechanism takes the crisp values as input variables such as trust threshold vector and packet arrival rate. In second phase, intrusion prevention system is established to isolate the attackers in the network. Based on the extensive simulation results, FIPS achieves more network performance in terms of intrusion detection ratio, throughput, delay and packet arrival rate.